BIOSYNTHESIS OF POLYHYDOXYALKANOATE - Idi, Ahmad (International Journal of Research -GRANTHAALAYAH, 2019)
Polydroxyalkanoate (PHA) is produced and stored as water-insoluble granules in the cytoplasm of many bacteria. It possesses similar physical properties to petroleum-based polyesters. Hence it is considered as degradable plastic that can replaced the petroleum-based polyesters. This article reviews the various processes involved in the biosynthesis, identification and characterisation of PHA. It covers both the presumptive and confirmatory test in the identification of PHA produced by bacteria as well as the various methods of PHA recovery. Techniques such as Nuclear Magnetic Resonance (NMR), Fourier Transform Infrared Spectroscopy (FTIR) and chromatography were discussed in relation to PHA characterisation. The identification of PHA producing bacteria and characterisation of PHA are significant for both quantitative and qualitative analysis of PHA.